Microarray analysis of gene expression profiles of pig muscle in response to cold stress - Zhang, Dongjie; Liu, Di; Wang, Liang; Wang, Wentao; He, Xinmiao; Yang, Guowei (The Indian Journal of Animal Sciences, 2012)
Ambient temperature is a critical factor that affects biological organisms in many ways. In this study, the authors investigated gene expression changes in Min pig muscle in response to cold stress. Female Min pigs were randomly divided into control and cold-stressed groups. Control group was housed at 10±2°C; the cold-stressed group was housed at –20±3°C for 13 days. The results showed that 34 genes were differentially expressed, of which 7 genes were significantly upregulated and 27 genes were significantly downregulated. Subsequent bioinformatics analyses revealed that the differentially expressed genes were mainly related to immune response, response to virus, and RNA binding. The bioinformatics analysis of the differentially expressed genes should be beneficial to further investigations on the underlying mechanisms involved in cold stress–induced damage in the muscle.